Mitigating land and place | Fifth Ward - LaMartina, Joshua (Kansas State University, 2009)
MDI Superfund is an abandoned 36 acre metal casting foundry site in the Fifth Ward Houston, TX. The site was recently remediated and cleared of nearly all industrial remnants including more than 16,000 cubic yards of lead contaminated soil. Completion of the remedial action allows the removal of fences that have been separating this tract of land and the community for nearly ten years. Proximity to downtown Houston makes this a desirable location for new development, which has threatened to displace the poor and elderly in recent years. This project explores design alternatives that facilitate affordable housing without isolating it from new development. The integration of affordable housing with community needs is necessary to improve the dynamic in a mixed use, mixed income development. This research is intended to shape redevelopment of MDI Superfund, while providing community needs, minimizing gentrification, and improving quality of life of its inhabitants. The achievement of these goals relies upon the application of specific design principles that minimize conflict and increase success in similar communities.
Keywords: brownfield; Houston; Fifth ward; mixed income; Landscape Architecture (0390)